Implementation of a Decision Support System Using the Simple Additive Weighting (SAW) Method in the New Student Admission Selection Process - Maya Oktarina; Nazori Suhandi; Indah Permatasari (Journal of Engineering Science and Technology Management, 2026)
The selection process for new student admissions in secondary schools is often manual and error-prone, so a web-based decision support system (DSS) is needed to improve objectivity and efficiency. This study aims to design and implement a DSS using the Simple Additive Weighting (SAW) method at SMK Negeri 1 Tanjung Lubuk. An applied quantitative approach with the Waterfall model was used; the population was all prospective students through three admission pathways, a sample of 23 purposive applicants. Instruments included academic data documents, interviews, and web input; data analysis via SAW (matrix normalization, criteria weighting, preference values). The results showed an accurate ranking with the highest score of 1.84 (Muhamad Angga Prayitno) based on five criteria (exam scores, report cards, KIP, achievement, distance). The conclusion states that the system increases transparency and speed of selection, and replication in other schools with broader testing is recommended.